The Impact of Digitalization to Accelerate Economic Performance During COVID-19 Pandemic - Alif Ihsan A Fahta; Anggita Fiorella Moreni; Adzrani Anggita (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2022)
The COVID-19 pandemic has affected various lines of life, especially the economy, not only in Indonesia in general but also in East Java Province in particular. The pandemic conditions limit human physical activity and make the use of digital technology increasingly massive. Using digital competitiveness data (EV-DCI), as well as other digitization indicators obtained from Badan Pusat Statistik (BPS), this study attempts to investigate the impact of digitization at the district/city level in East Java Province and at the provincial level in Indonesia on regional economic performance indicated with an increase in GDP per capita. From the OLS method used, it was found that increasing the use of internet access at the city/district level in East Java Province can significantly increase GRDP per capita. Furthermore, the researcher also uses the 2SLS method in analyzing the impact of digital competitiveness on improving economic performance at the provincial level. Similar results were found where increasing digital competitiveness can significantly improve economic performance. Through qualitative analysis, this study suggests relevant policymakers, especially in the East Java Province, encourage digitization, one of which is through the adoption of e-commerce by MSMEs.